LTE‐based satellite communications in LEO mega‐constellations. (10th July 2018) - Guidotti, Alessandro; Vanelli‐Coralli, Alessandro; Foggi, Tommaso; Colavolpe, Giulio; Caus, Márius; Bas, Joan; Cioni, Stefano; Modenini, Andrea
Summary: The integration of satellite and terrestrial networks is a promising solution for extending broadband coverage to areas not connected to a terrestrial infrastructure, as also demonstrated by recent commercial and standardisation endeavours. However, the large delays and Doppler shifts over the satellite channel pose severe technical challenges to traditional terrestrial systems, as long‐term evolution (LTE) or 5G. In this paper, 2 architectures are proposed for a low Earth orbit mega‐constellation realising a satellite‐enabled LTE system, in which the on‐ground LTE entity is either an eNB (Sat‐eNB) or a relay node (Sat‐RN). The impact of satellite channel impairments as large delays and Doppler shifts on LTE PHY/MAC procedures is discussed and assessed. The proposed analysis shows that, while carrier spacings, random access and RN attach procedures do not pose specific issues and hybrid automatic repeat request requires substantial modifications. Moreover, advanced handover procedures will be also required due to the satellites' movement. Abstract : This paper focuses on the definition of a LTE–based SatCom system through Low Earth Orbit mega–constellations to extend broadband coverage to areas not connected to a terrestrial infrastructure by proposing 2 system architectures. The impact of typical satellite channel impairments on LTE PHY/MAC procedures is assessed. Our analysis shows that, while carrier spacings, random access, and Relay Node attach procedures do not pose specific issues, Hybrid Automatic Repeat reQuest requires substantial modifications. Moreover, advanced handover procedures will be also required due to the satellites' movement.